Strategies for Fostering Religious Character in Adolescents: An Analysis of IPNU-IPPNU's BRUS Program - Ardiati, Syarifah Setiana; Hinayatulohi , Ahmad (Mimbar Ilmu, 2024)
This research is motivated by the phenomenon of increasingly massive globalization and digitalization, religious values often experience degradation due to the influence of external cultures that are not in line with local norms and traditions, this has a major impact on increasing juvenile delinquency, such as brawls, drug abuse, promiscuity, and other violations of the law. This study aims to analyze the strategies implemented by IPNU-IPPNU in forming religious character in adolescents through the BRUS program. This study uses a combination method (mixed methods), with data collection techniques through observation, interviews, documentation studies, and surveys. The collected data were analyzed using three main steps, namely data condensation, data presentation, and drawing conclusions. The results of the study show that the strategies carried out by IPNU-IPPNU in forming religious character include three stages: first, strategic planning, which includes problem identification, needs analysis, strategy analysis, and activity design; second, strategy implementation, which involves Training of Facilitators and implementation of the BRUS program in educational institutions; Third, Evaluation of the enthusiasm and understanding of the participants also showed positive results, Conclusion This study shows that the BRUS program implemented by IPNU-IPPNU in Singaparna, Tasikmalaya, has a significant impact on the development of adolescent religious character. The implications of these results can be the basis for developing better programs in the future.